2014
DOI: 10.1159/000356539
|View full text |Cite
|
Sign up to set email alerts
|

The Immunology of Bipolar Disorder

Abstract: Bipolar disorder (BD) is a psychiatric condition associated with elevated frequency of clinical comorbidities and cognitive impairment. The neurobiology of BD is not completely understood. Recent evidence has implicated immune dysfunction in its physiopathology. Here, we review several data supporting the presence of immunological dysfunction in BD: (i) increased frequency of autoimmune diseases; (ii) distinct immune cell profile; (iii) release of/altered cytokines by stimulated mononuclear cells; (iv) elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(64 citation statements)
references
References 44 publications
0
64
0
Order By: Relevance
“…A possible explanation for these observations centers on the role of the cytokine IFN-γ, which is required for neopterin release from monocytes/macrophages (Murr et al, 2002). IFN-γ release has been reported to be lower in BD (Barbosa et al, 2014). In this way, perhaps neopterin is not being stimulated for release in our BD group.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for these observations centers on the role of the cytokine IFN-γ, which is required for neopterin release from monocytes/macrophages (Murr et al, 2002). IFN-γ release has been reported to be lower in BD (Barbosa et al, 2014). In this way, perhaps neopterin is not being stimulated for release in our BD group.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of bipolar disorder has yet to be well understood, while recent studies have indicated abnormal immunological functions may be a contributing factor (1, 2). Microglia, immune cells in the brain, play important roles in the process of brain inflammation, and recent positron emission tomography (PET) studies have shown microglial overactivation in the brain of patients with various psychiatric disorders including bipolar disorder (38).…”
Section: Bipolar Disorder and Microgliamentioning
confidence: 99%
“…These effects lead to the destruction or atrophy of neurons and loss of glial elements [96]. CNS-derived cytokines produce similar responses [97]. …”
Section: Inflammation Pathwaymentioning
confidence: 99%